Anthracene- pentacene dyads: synthesis and OFET characterization - Hauschild, Miriam; Chen, Lan; Etschel, Sebastian H.; Ferguson, Michael J.; Hampel, Frank; Halik, Marcus; Tykwinski, Rik R. (ChemPlusChem, 2020)
The synthesis of a series of unsymmetrical derivatives of pentacene appended with functionalized anthracene moieties is reported. These anthracene−pentacene dyads have been characterized by UV-vis spectroscopy and cyclic voltammetry to examine their electronic properties. X-ray crystallographic analysis was used to examine the solid-state features of anthracene−pentacene dyads 1 a-d with H−, F−, Cl−, and Br− substituents on the 9-position of anthracene, and shows that the packing arrangement of anthracene−pentacene derivatives 1 b,d,e are remarkably similar irrespective of the presence of fluoride, bromide or methyl substituents. The pentacene−anthracene dyads have been incorporated into OTFTs to evaluate their semiconducting properties. The pentacene derivative 1 b shows ambipolar behavior using AlOx C14PA as the gate dielectric (electron and hole mobilities of 7.6 ⋅ 10−3 and 1.6 ⋅ 10−1 cm2 V−1 s−1), while performance of all derivatives was poor using p-doped Silicon as the substrate. These studies highlight the importance of thin-film formation over molecular structure.